Constructivist Approaches in Arabic Language Teaching: An Analysis of the Relationship with Modern Linguistic Theories - Ahmad Ridho; Husnul Haq (IJAS: International Journal of Arabic Studies, 2024)
This study explores the application of constructivist approaches in Arabic language teaching and examines their relationship with modern linguistic theories. The primary objectives are to investigate how constructivist principles are implemented in Arabic classrooms and evaluate their effectiveness in enhancing students' language skills. Additionally, the study analyzes how cognitive and generative-transformational theories are integrated into these teaching methods. The findings reveal that constructivist approaches, such as project-based learning and collaborative activities, significantly improve student engagement, motivation, and language proficiency. Cognitive strategies, including metacognitive activities, and problem-solving tasks are effectively employed to support learning. Furthermore, generative-transformational theory influences the teaching of Arabic syntax and grammar, enhancing students' understanding of language structures. The study concludes that combining constructivism with modern linguistic theories offers valuable insights for improving language instruction. Practical recommendations for educators include incorporating constructivist strategies and theoretical principles to enhance teaching effectiveness.